Clinical advances in transcutaneous auricular vagus nerve stimulation for post-stroke disorders: state of the art and future perspectives - Sun, Jifei; Li, Xuefei; Zhou, Yuan; Liu, Hongwei; Ma, Chenjie; Hao, Chunbo; Liu, Shuqing; Zhao, Jingxue; Zhang, Xiaojian; Xiao, Xue (Frontiers in Neurology, 2025)
Transcutaneous auricular vagus nerve stimulation (taVNS) has emerged as a promising non-invasive neuromodulation therapy for post-stroke disorders. This review synthesizes current evidence on the clinical efficacy and underlying mechanisms of taVNS in addressing a spectrum of post-stroke disorders, including motor, sensory, neuropsychiatric, and cognitive impairments. By targeting the auricular branch of the vagus nerve, taVNS modulates central pathways involved in neuroplasticity, anti-inflammation, angiogenesis, and blood–brain barrier protection, offering a multifaceted approach to stroke rehabilitation. Clinical studies demonstrate its potential to enhance functional recovery and improve quality of life, supported by its favorable safety profile and patient compliance. However, challenges such as parameter standardization, mechanistic elucidation, and individualized protocols remain. Future research should focus on large-scale trials, mechanistic exploration, and technological innovations to optimize taVNS applications in stroke care.